ANALISIS KEMAMPUAN PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL INTERAKTIF DITINJAU DARI GURU PENGGERAK GUGUS 2 SDN SE-KECAMATAN DURENAN - Ismi Rahmawati; Kukuh Andri Aka; Frans Aditia Wiguna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the ability of driving teachers and non driving teachers of Cluster 2 elementary schools throughout Durenan District in using interactive digital learning media, as well as to determine the differences in the ability to use interactive digital learning media between driving teachers and non driving teachers of Cluster 2 elementary schools throughout Durenan. This study uses a quantitative approach with a comparative descriptive method. The instrument used was a questionnaire given to two groups of respondents, each consisting of 10 driving teachers and 10 non-driving teachers. Based on the results obtained, there is a difference in the ability to use interactive digital learning media between driving and non-driving teachers, seen from the results of the Mann-Whitney test, a significance value of 0.000 (> 0.05) was obtained, which indicates that there is a difference in the ability to use interactive digital media.